2017
DOI: 10.1055/s-0036-1597811
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Digital Radiography for Diagnosis of Fishbone Foreign Bodies in the Throat

Abstract: Introduction  Some patients with a fishbone as a foreign body of difficult diagnosis may require further investigations. Generally, radiography is used as the first choice for finding the fishbone. Objective  The objective of this study is to determine the accuracy of digital radiography for diagnosis of fishbone foreign body in the throat Methods  This descriptive experimental study design has three phases. In the first phase, we assessed subject contrast and visibility of fishbone on a homogeneous backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Kasemsiri et al believe that the inhalation of foreign bodies in children will cause great pain to children, and the more serious ones may even be life-threatening. He proposed that CT imaging technology can reduce the chance of misdiagnosis or missed diagnosis when diagnosing foreign bodies in the respiratory tract so that more children can be as early as possible and accurately diagnose the foreign body in the respiratory tract [ 3 ]. Egorov and Mustafaev and others conducted a questionnaire survey on 1490 mothers of children under the age of 2 to learn their understanding of nut-like respiratory foreign bodies, which proved that parents generally lack the awareness of preventing accidental injury of children's respiratory foreign bodies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kasemsiri et al believe that the inhalation of foreign bodies in children will cause great pain to children, and the more serious ones may even be life-threatening. He proposed that CT imaging technology can reduce the chance of misdiagnosis or missed diagnosis when diagnosing foreign bodies in the respiratory tract so that more children can be as early as possible and accurately diagnose the foreign body in the respiratory tract [ 3 ]. Egorov and Mustafaev and others conducted a questionnaire survey on 1490 mothers of children under the age of 2 to learn their understanding of nut-like respiratory foreign bodies, which proved that parents generally lack the awareness of preventing accidental injury of children's respiratory foreign bodies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our Case 2 showed that not all FB can be visualized using plain neck radiograph and it is thus not reliable to detect FB. The decreased visibility of fish bone on radiograph maybe a consequence of a few factors, including the inherent radio-opacity of different species of fish bone, lodgment site, diameter and human laryngeal ossification [9,10]. Moreover, it also could not help to determine the migration of FB and unable to pinpoint the precise location of a FB.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have revealed poor sensitivity and specificity of this imaging modality. 1 2 7 8 9 10 And the fact that the bones of different species of fish vary in degree of opacification under plain film leads to doubt about the usefulness of this modality. Computed tomography (CT) has emerged as an optional imaging modality to evaluate foreign body retention.…”
Section: Introductionmentioning
confidence: 99%